2017
DOI: 10.5812/jssc.68333
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sesame Oil and Cucurbita on Healing Wounds Caused by Third-Degree Burn

Abstract: Background: Previous in vitro studies showed that sesame oil stimulates fibroblast production in wounds. Many studies investigated the therapeutic wound healing properties of natural products. The current study aimed at evaluating the effect of the combination of sesame oil and Cucurbita as a novel herbal mixture on healing the local wounds caused by the third-degree burn. Methods: The current experimental study was conducted on 24 adult BALB/c mice randomly divided into experimental groups. Then, all mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In this study, we evaluated the effect of Sesame oil stimulates fibroblast production in wounds. 16 The current study results showed that a combination of sesame oil and herbal plants at different concentrations accelerated the healing process of burn wounds in rats especially at concentrations 2.5% sesame oil.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, we evaluated the effect of Sesame oil stimulates fibroblast production in wounds. 16 The current study results showed that a combination of sesame oil and herbal plants at different concentrations accelerated the healing process of burn wounds in rats especially at concentrations 2.5% sesame oil.…”
Section: Discussionmentioning
confidence: 55%
“…Sesame oil may accelerate ulcerated lesion healing by shortening the inflammation phase and promoting the proliferation phase. 14 So, KEM CON ONG and KEM TRI BONG contain ingredients that have healing effect on the ulcerated skin. The two creams have a common ingredient which is seasame oil but in different concentration.…”
Section: Effect On Liver Functionmentioning
confidence: 99%